2019
DOI: 10.16923/reb.v17i2.869
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Educational Games to Explain Complex Concepts Related to Human Physiology

Abstract: Different strategies have been proposed to improve the teaching-learning process in different fields. One option to optimize learning, increasing students' involvement and providing group discussions, is the use of educational games (EG). In this study, we evaluated the students' perceptions about the use of EG as a tool to facilitate the understanding of key concepts related to Human Physiology (HP). Educational games addressing the bioelectric membrane potential and the cardiac cycle were used to complement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…On one hand, our study agrees with the finding of Selby et al (45) that showed better scores in multiple-choice tests of medical students who received interactive classes about children's development compared to those who received the content through games. By contrast, das Neves et al (12) reported that educational games about the membrane potential and the cardiac cycle were well accepted by nursing and physiotherapy students in the subject of human physiology, in addition to being perceived as useful tools for enhance learning. These differences observed both for this teaching strategy (educational games) as well as for other active learning methods, could be the result of a combination of specific variables in each cohort studied, among which the following factors can influence the appropriate development of each methodology or teaching strategy and the students satisfaction: experience and ability of the facilitator, tutorials on the structure of the methodology, authenticity of the case analyzed in the classroom, availability of information sources, individual student factors (e.g.…”
Section: Learningmentioning
confidence: 94%
“…On one hand, our study agrees with the finding of Selby et al (45) that showed better scores in multiple-choice tests of medical students who received interactive classes about children's development compared to those who received the content through games. By contrast, das Neves et al (12) reported that educational games about the membrane potential and the cardiac cycle were well accepted by nursing and physiotherapy students in the subject of human physiology, in addition to being perceived as useful tools for enhance learning. These differences observed both for this teaching strategy (educational games) as well as for other active learning methods, could be the result of a combination of specific variables in each cohort studied, among which the following factors can influence the appropriate development of each methodology or teaching strategy and the students satisfaction: experience and ability of the facilitator, tutorials on the structure of the methodology, authenticity of the case analyzed in the classroom, availability of information sources, individual student factors (e.g.…”
Section: Learningmentioning
confidence: 94%